Clinical application of multicolor scanning laser ophthalmology in diagnosis and grading of central retinal artery occlusion - Wan, Yuwei; Chen, Ting; Li, Ying; Yang, Yang; Wang, Yaqi; Wang, Yuedan; Li, Xuejie; Yang, Anhuai; Xiao, Xuan (Frontiers in Neuroscience, 2024)
Purpose. To characterize features of Central retinal artery occlusion (CRAO) using multicolor (MC) imaging and to assess the differences in CRAO grading between color fundus photography (CFP) and MC image. Methods. We conducted a prospective, cross-sectional study in Department of Ophthalmology of Renmin Hospital of Wuhan University. 86 acute CRAO patients were included. Spectral-domain optical coherence tomography (SD-OCT), CFP, and MC examinations were taken at baseline. Based on the findings of three examinations, CRAO was divided into three grades. Based on OCT grading criteria, we compared ability of grading CRAO by CFP and MC. CRAO patient's visual acuity(VA) obtained from initial visit. Retinal thickness was measured by SD-OCT. Superficial capillary plexus (SCP) and deep capillary plexus (DCP) were got from optical coherence tomography angiography (OCTA) examinations. Data were compared across three CRAO subgroup and against three examinations findings. Results. MC image had significant higher power of acute CRAO detection than CFP (P =0.03). In the same group of CRAO patients, there was no significant difference in VA when comparing OCT with MC grading system or with the CFP grading system(All P>0.05). Significance differences in VA were found between three CRAO subgroups only under MC grading.(P=0.016). In incomplete CRAO patients, significant differences were found in central fovea thickness （CFT）when comparing OCT with CFP grading system(P=0.019). In the same group of CRAO patients, there was no significant difference in retinal thickness when comparing OCT with MC grading system (All P>0.05). Significance differences in CFT (P<0.001), innermost retinal layer (IMRL)(P<0.01), middle retinal layer (MRL)(P<0.001) and outer retinal layer (ORL)(P=0.021) were found between three CRAO subgroups by MC grading. Vessel density of SCP showed statistically increased as the severity of three CRAO subgroups (P =0.03), whereas DCP was not significant differences (P=0.745). Comparisons were made between OCT grading method and MC and CFP grading method, there is no significant difference in SCP and DCP (All P>0.05). Conclusion. The image obtained by MC are superior to that obtained by CFP in CRAO grading, retinal thickness and vessel density measurement. We recommend MC imaging to determine CRAO severity to guide disease treatment and predict visual prognosis.